Section 3 of the Refugee Act: non-recognition of gender as a claim for refugee status in Kenya - Kobia, M. (Strathmore University, 2024)
Gender-based violence (GBV) remains a pervasive societal issue, influenced by various factors including patriarchal structures, gender disparities, cultural norms, and lack of awareness. Despite its severity as a human rights violation, the 1951 Refugee Convention does not explicitly address GBV as a protected ground. However, the UNHCR's guidelines recognize GBV as a distinct form of persecution, calling for gender-sensitive approaches to refugee status determination. This dissertation examines the impact of the exclusion of gender as a basis for seeking asylum under Kenya's Refugees Act 2021 on GBV survivors' rights and protection. Through a feminist theoretical framework, the study investigates the interconnectedness of GBV, refugee law, and gender dynamics, highlighting the need for a gender-sensitive approach in refugee status determination. It also analyzes international and domestic legal frameworks, exploring the gaps in recognizing GBV as a valid claim for refugee status. Utilizing literature reviews and legal analysis, the study aims to shed light on the challenges faced by GBV survivors seeking asylum and advocate for the explicit inclusion of gender in Kenya's Refugee Act. The research objectives focus on examining the relationship between refugee law and GBV, investigating the human rights implications of excluding gender as a basis for asylum, analyzing the impact of this exclusion on systemic disparities, and assessing the effects on Refugee Status Determination processes. By proposing the inclusion of gender-based violence as a valid basis for seeking refugee status in Kenya, this study seeks to rectify systemic injustices faced by GBV survivors and contribute to a more inclusive and protective refugee law framework.
Full - text undergraduate research project